Comprehensive Stroke Care and Outcomes: Time for a Paradigm Shift. Issue 1 (January 2021) - Duncan, Pamela W.; Bushnell, Cheryl; Sissine, Mysha; Coleman, Sylvia; Lutz, Barbara J.; Johnson, Anna M.; Radman, Meghan; Pvru Bettger, Janet; Zorowitz, Richard D.; Stein, Joel
Abstract : Worldwide, stroke is prevalent, costly, and disabling in >80 million survivors. The burden of stroke is increasing despite incredible progress and advancements in evidence-based acute care therapies and despite the substantial changes being made in acute care stroke systems, processes, and quality metrics. Although there has been increased global emphasis on the importance of postacute stroke care, stroke system changes have not expanded to include postacute care and outcome follow-up. Our objectives are to describe the gaps and challenges in postacute stroke care and suboptimal stroke outcomes; to report on stroke survivors' and caregivers' perceptions of current postacute stroke care and their call for improvements in follow-up services for recovery and secondary prevention; and, ultimately, to make the case that a paradigm shift is needed in the definition of comprehensive stroke care and the designation of Comprehensive Stroke Center. Three recommendations are made for a paradigm shift in comprehensive stroke care: (1) criteria should be established for designation of rehabilitation readiness for Comprehensive Stroke Centers, (2) The American Heart Association/American Stroke Association implement an expanded Get With The Guidelines–Stroke program and criteria for comprehensive stroke centers to be inclusive of rehabilitation readiness and measure outcomes at 90 days, and (3) a public health campaign should be launched to offer hopeful and actionable messaging for secondary prevention and recovery of function and health. Now is the time to honor the patients' and caregivers' strongest ask: better access and improved secondary prevention, stroke rehabilitation, and personalized care.